Effects of Systolic Blood Pressure on Brain Integrity in Multiple Sclerosis - Dossi, Daiana E.; Chaves, Hernán; Heck, Evelyn S.; Rodriguez Murúa, Sofía; Ventrice, Fernando; Bakshi, Rohit; Quintana, Francisco J.; Correale, Jorge; Farez, Mauricio F. (Frontiers in Neurology, 2018)
Background In MS patients, hypertension is associated with a delayed diagnosis and an increased risk of progression. Understanding the mechanisms of this association could potentially lead to improved prevention of disease progression. We aimed to establish whether high blood pressure contributes to white-matter injury and brain atrophy in MS. Methods Cross-sectional study of 95 patients with RRMS. Estimates of fractional anisotropy, grey-matter volume and lesion load were obtained from 3T MRI. We used fractional anisotropy voxel-based statistics to establish the effect of blood pressure on white matter tracts. Additionally, we used voxel-based morphometry to study the effect on grey matter integrity. Results Only 29.5% had normal blood pressure levels, with 52.6% suffering from prehypertension and 17.9% with hypertension. Increasing systolic blood pressure was associated with damage to posterior white-matter tracts as well as greater levels of grey matter atrophy, in particular in the frontal cortex. Age-adjusted linear regression indicated that neither lesion volume (β=0.002,95%CI-0.02-0.02; p=0.85) or lesion number (β=-0.004,95%CI-0.03-0.02; p=0.74) were associated with systolic blood pressure. Conclusions Prehypertension and hypertension are frequent in MS. Increased blood pressure is related to white- and grey-matter integrity, both related to MS disability outcomes. These findings suggest attention to the control of blood pressure in MS patients.